Toxic Effects of Ethyl Cinnamate on the Photosynthesis and Physiological Characteristics of Chlorella vulgaris Based on Chlorophyll Fluorescence and Flow Cytometry Analysis - Jiao, Yang (ScientificWorldJournal, 2015)
The toxic effects of ethyl cinnamate on the photosynthetic and physiological characteristics of Chlorella vulgaris were studied based on chlorophyll fluorescence and flow cytometry analysis. Parameters, including biomass, F (v)/F (m) (maximal photochemical efficiency of PSII), Ф(PSII) (actual photochemical efficiency of PSII in the light), FDA, and PI staining fluorescence, were measured. The results showed the following: (1) The inhibition on biomass increased as the exposure concentration increased. 1 mg/L ethyl cinnamate was sufficient to reduce the total biomass of C. vulgaris. The 48-h and 72-h EC50 values were 2.07 mg/L (1.94–2.20) and 1.89 mg/L (1.82–1.97). (2) After 24 h of exposure to 2–4 mg/L ethyl cinnamate, the photosynthesis of C. vulgaris almost ceased, manifesting in Ф(PSII) being close to zero. After 72 h of exposure to 4 mg/L ethyl cinnamate, the F (v)/F (m) of C. vulgaris dropped to zero. (3) Ethyl cinnamate also affected the cellular physiology of C. vulgaris, but these effects resulted in the inhibition of cell yield rather than cell death. Exposure to ethyl cinnamate resulted in decreased esterase activities in C. vulgaris, increased average cell size, and altered intensities of chlorophyll a fluorescence. Overall, esterase activity was the most sensitive variable.